A percepção do processo de silenciamento em ambiente escolar por alunos de instituições públicas de Alfenas - MG - Ferreira, Reginaldo (2018)
The present dissertation, whose theme is " The Perception of the Process of Silencing in School Environment by students of Public Institutions of Alfenas - MG", intends to verify if the Brazilian public school acts in an effective and institutionalized way to maintain an informal process of silencing the students, ascertaining if their practices are Dialogical or monological. It is understood, in this dissertation, democracy in its broader sense of right to voice, that is, the maintenance of a real dialogue. What our experience as an educator has attested, however, is that students are often silenced under the allegation of teacher authority or the maintenance of the school hierarchy which, in its exercise of power with institutional protection, only establishes standards that Students should follow, with no possibility of dialogue. It is common to see that the student is only in the classroom because he has been forced to be, since the school has not offered enough elements to awaken the creativity, imagination, pleasure and the desire to share the contents released in the classroom of class. The educational model presented today has been very ineffective. Therefore, it is worth investigating to what extent this system imposes a teaching-learning model that does not fit with the proposal of democratic education. For this, the focus of this research was the perception that the students of different levels of Basic Education have of the question of the silencing, verifying if they consider that the school worries about the dialogue or if it exercises a monologic educative practice and establishes a ordenation in which Only the speeches of the school are valid. The results show that, from the point of view of the students, they are silenced by the teachers' voice and by other constituent elements of the formal school system. This allowed us to elucidate the extent to which these students cease to be active agents of their knowledge to be passive recipients of the content imposed by educators.